2015
DOI: 10.1007/s11695-014-1548-8
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory and Metabolic Response in the Incremental Shuttle and 6-Min Walking Tests Measured by Telemetry in Obese Patients Prior to Bariatric Surgery

Abstract: The ISWT test generated superior metabolic and ventilatory stress than the 6MWT and may be more suitable for assessing cardiopulmonary fitness than self-paced tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
5
1
2
Order By: Relevance
“…Evans et al ( 22 ) compared the cardiopulmonary responses of both the ISWT and 6-min walk test (6MWT) with CPX results in an obese cohort (men and women with a mean BMI of 33.3 kg/m 2 , similar to our study) with obstructive sleep apnea and found a stronger relationship (r=0.87, P<0.001) between ISWT distance and peak VO 2 during CPX compared to our findings. Oliver et al ( 23 ) compared the metabolic responses during the ISWT and 6MWT in obese patients prior to bariatric surgery (BMI: 43.5 kg/m 2 ). The authors found that the ISWT induced a higher metabolic demand compared to the 6MWT.…”
Section: Discussionmentioning
confidence: 99%
“…Evans et al ( 22 ) compared the cardiopulmonary responses of both the ISWT and 6-min walk test (6MWT) with CPX results in an obese cohort (men and women with a mean BMI of 33.3 kg/m 2 , similar to our study) with obstructive sleep apnea and found a stronger relationship (r=0.87, P<0.001) between ISWT distance and peak VO 2 during CPX compared to our findings. Oliver et al ( 23 ) compared the metabolic responses during the ISWT and 6MWT in obese patients prior to bariatric surgery (BMI: 43.5 kg/m 2 ). The authors found that the ISWT induced a higher metabolic demand compared to the 6MWT.…”
Section: Discussionmentioning
confidence: 99%
“…The rise in VE could be related to the increase of VO2max-HRmax because of high intensity of a maximal cardio-pulmonary exercise which is related with VO2max relative according to American Thoracic Society (ATS) and American College of Chest Physicians (ACCP) 23 . The Oliver et al 27 study where the increase of VE was related to maximal capacity exercise, showed similar physiologic parameters with participants of similar age but more weight. The results of the present study prove that respiratory system represents a limiting factor during the physical activity, especially in elderly people.…”
Section: Discussionmentioning
confidence: 77%
“…Im randomisierten Vergleich zwischen 6-MWT, inkrementalem Shuttle-Walk-Test (ICSWT) bzw. inkrementalem Laufbandtest (ITMT) waren bei adipösen Patienten (Grad I-III) mit behandelter obstruktiver Schlafapnoe bei den inkrementalen Tests der Anstieg von V O 2 während der Belastung linear und peak V O 2 höher als beim 6-MWT [354,355].…”
Section: Einfluss Der Adipositas Auf Die Körperliche Leistungsfähigkeitunclassified